The work-related experiences of the registered nurses working in a correctional services healthcare facility in Gauteng - Nkosi, Muntu (My University, 2016)
Correctional services nurses hold a unique position through serving the demands of two departments, namely correctional services and health care. In addition, limited research has been done on the experiences of registered nurses working in a unique environment like correctional services. A qualitative, exploratory and descriptive study was conducted through 21 semi-structured interviews to identify the work-related experiences of the registered nurses working in a correctional services healthcare facility in Gauteng. This was conducted in order to make recommendations for the improvement of the working conditions of these registered nurses. Thematic analysis was used to analyse the data. The following three themes were identified on the positive experiences: These were the provision of education and in-service training, positive team work and good working relationships among registered nurses and improved access to healthcare services and upholding the rights of inmates. Under the negative experiences these were the six themes that were identified: The impact of work overload related to overcrowding, insufficient policies on the care rendered to inmates, security being a priority over health, mismanagement of inmates due to incorrect medical history and procedures, Insufficient medication, medical supplies, equipment and infrastructure and lack of transportation to provide for the needs of the inmates. This shows that the registered nurses had more negative than positive work-related experiences. Recommendations for the improvement of the registered nurses’ working conditions were made.
A research report submitted to the Faculity of Health Sciences of the University of the Witwatersrand in Fulfiment of the requirements for the Degree of Master of Science in nursing Johannesburg, 2016.